32860-0.06x=x

Simple and best practice solution for 32860-0.06x=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 32860-0.06x=x equation:


Simplifying
32860 + -0.06x = x

Solving
32860 + -0.06x = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
32860 + -0.06x + -1x = x + -1x

Combine like terms: -0.06x + -1x = -1.06x
32860 + -1.06x = x + -1x

Combine like terms: x + -1x = 0
32860 + -1.06x = 0

Add '-32860' to each side of the equation.
32860 + -32860 + -1.06x = 0 + -32860

Combine like terms: 32860 + -32860 = 0
0 + -1.06x = 0 + -32860
-1.06x = 0 + -32860

Combine like terms: 0 + -32860 = -32860
-1.06x = -32860

Divide each side by '-1.06'.
x = 31000

Simplifying
x = 31000

See similar equations:

| 7y+5=6y | | -43+11x=6x+32 | | -2k-16=3h-6 | | 2(x+4)=12x+62 | | 46=-6-8 | | 269.50=14 | | X-.4x=60 | | 20x+10y=0 | | 19-11n+16n-4= | | 9u^2+1u-10=0 | | X-x(.4)=60 | | 20x+10y=107 | | 3x+10=6x-19 | | 3z+1=34 | | -42-10x=53-5x | | 6x+9=4(-x) | | x^2(2x+3)+2x(3x^2+5x)= | | 24-2t-t^2=0 | | x^3+3x^2=4x-12 | | 15-(-7x)+5x-(-9)= | | 8*n=56 | | X^3-7x-18x=0 | | 7-y-6=-1 | | (n-6)+12=24 | | 6x-48=46 | | 8e+(5-e)=30 | | 7a+8b=11-5c | | -134-2x=-10x+58 | | 6*-48=46 | | 20=140 | | 3x^2=3x+60 | | 2(3d+6)=24 |

Equations solver categories